Comparación de perfiles de disolución de diazepam en tabletas 10 mg utilizando modelos independientes” - Alva Bocanegra, Ronald (2009)
The aim of this study was to compare the dissolution profiles of generic Diazepam tablets 10 mg - Lab Farmindustria and Valium® 10 mg Lab ROCHE using independent models, the dissolution profiles of both formulations was characterized in three media: 0.1 N HCl pH 1.2, acetate buffer pH 4.5 and pH 6.8 phosphate buffer, according to the protocol of bioequivalence studies in vitro established by WHO. The amounts dissolved temporary analyzed by the ANOVA model and applied a statistical analysis ( t Student) independent models, average time of solution (TMD), half-life of dissolution (t50%), efficiency of dissolution (ED%) obtained for tablets of Diazepam VALIUM® 10mg and 10mg generic tablets. The statistical comparison of the various parameters determined a statistically significant difference (p <0.05) in the three media studied. Conclude that the dissolution profiles of generic diazepam 10 mg tablets Lab. Farmindustria and Valium® 10 mg - Lab ROCHE are not similar.